Bioactive Restorative Materials Beyond Remineralization: Can Restorations Become Therapeutic Devices? - Zavielis Maldonado Zavielis Maldonado; Kennard William Vandergrift Kennard William Vandergrift; Yerennis Campaneria Yerennis Campaneria; Anabel Calero Pardo Anabel Calero Pardo; Cindy Maura Dorta Cindy Maura Dorta; Hilary Pimentel Hilary Pimentel (International Journal of Research in Medical and Clinical Science, 2026)
Bioactive restorative materials mark an important shift in restorative dentistry, moving beyond the replacement of lost tooth structure to materials that actively interact with dental tissues and the oral environment. This narrative review examined evidence published between 2021 and 2026 on ion release, remineralization, antibacterial activity, biofilm modulation, self-healing, and environmental responsiveness, and considered whether contemporary materials perform functions that extend beyond structural replacement. Ion-releasing systems modify the tooth-material interface and support remineralization of caries-affected tissue, while antibacterial formulations limit bacterial colonization and secondary caries. Responsive materials react to stimuli such as pH, whereas smart systems combine responsiveness with additional therapeutic functions. Self-healing composites, based mainly on microcapsule systems, remain largely experimental. Across categories, most supporting data come from laboratory and short-term investigations, and few materials demonstrate sustained clinical biological effects. Long-term randomized trials are required before these materials can be regarded as genuine therapeutic devices for routine restorative practice.